Nursing Manager Experience in the Covid-19 Pandemic Disaster Situation at RSUP H. Adam Malik (Proceeding International Collaborative Conference on Multidisciplinary Science, 2024)
The COVID-19 pandemic that began in late 2019 has brought major changes to various aspects of life, including the health sector. As the frontline in providing services, nursing managers have an important role in managing human resources, patient care flows, and maintaining the safety and health of medical personnel. This study aims to explore the experiences of nursing managers in dealing with the COVID-19 pandemic disaster situation, as well as the strategies they use to manage the challenges that arise. The method used in this study is a qualitative approach with a descriptive phenomenological design. A total of 10 nursing managers working in the emergency room participated in in-depth interviews to explore their experiences during the pandemic. The results of the study identified five main themes, namely: (1) Challenges in human resource management, (2) The role of leadership and effective communication, (3) Innovation and adaptation in care protocols, (4) Psychological support for nursing staff, and (5) Learning and preparedness for the future. This study shows that nursing managers have a very vital role in dealing with the crisis during the pandemic, with effective management, open communication, and attention to the psychological well-being of staff being the keys to success in maintaining quality of care amidst heavy workloads. These findings are expected to provide deeper insight into the role of nursing managers in global health disaster situations and provide recommendations for improving future preparedness.